2019
DOI: 10.5694/mja2.50285
|View full text |Cite
|
Sign up to set email alerts
|

The Australian Aboriginal Birth Cohort study: socio‐economic status at birth and cardiovascular risk factors to 25 years of age

Abstract: Objectives To determine whether socio‐economic status at birth is associated with differences in risk factors for cardiovascular disease — body mass index (BMI), blood pressure, blood lipid levels — during the first 25 years of life. Design Analysis of prospectively collected data. Setting, participants 570 of 686 children born to Aboriginal mothers at the Royal Darwin Hospital during 1987–1990 and recruited for the Aboriginal Birth Cohort Study in the Northern Territory. Participants resided in 46 urban and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…This is in contrast to a study from New South Wales that examined Indigenous people aged 45 years and older, where participants from more advantaged and urban surroundings had lower prevalences of obesity and overweight than those from remote and disadvantaged areas 16. In a previous study from the ABC, a significant association was found between remoteness and areal disadvantage at birth and longitudinal development of BMI measured at the same follow-ups as the present study 33. It seems that the spatial trend in obesity in this cohort is similar to that traditionally seen in low-income and middle-income countries, where obesity is more concentrated in cities and wealthier regions and underweight is more common in remote and rural settings 1.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to a study from New South Wales that examined Indigenous people aged 45 years and older, where participants from more advantaged and urban surroundings had lower prevalences of obesity and overweight than those from remote and disadvantaged areas 16. In a previous study from the ABC, a significant association was found between remoteness and areal disadvantage at birth and longitudinal development of BMI measured at the same follow-ups as the present study 33. It seems that the spatial trend in obesity in this cohort is similar to that traditionally seen in low-income and middle-income countries, where obesity is more concentrated in cities and wealthier regions and underweight is more common in remote and rural settings 1.…”
Section: Discussioncontrasting
confidence: 99%
“…Other maternal factors (two studies). In LSIC, higher maternal age was associated with higher BMI in preschool and childhood [ 58 ] and in ABC, higher maternal parity was associated with lower BMI during youth [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, greater area-level SES was associated with higher obesity measures. In ABC and LSIC, higher BMI or levels of obesity were consistently seen among children and youth who were living in more advantaged areas at baseline [ 46 , 47 , 49 , 52 , 53 , 56 ]. For example, LSIC participants from areas with highest disadvantage had 80% lower odds of obesity in childhood compared to the least disadvantaged areas [ 56 ], and ABC participants from least disadvantaged areas had 91% lower odds of ideal BMI at 25 years of age compared to most disadvantaged areas [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing studies have given insights into socioeconomic factors for the potential "longterm" effects on biological, psychological and behavioral factors of T2DM and attached great importance to childhood socioeconomic status (CSES) over the life course (3). Disadvantaged CSES 3 have been revealed as a salient predictor of later health, which is associated with majority chronic diseases occurring in mid-late adulthood such as cardiovascular disease (4), hypertension (5), functional limits (6), stroke (7) and cognitive impairment (8).…”
Section: Introductionmentioning
confidence: 99%